Symposium 5: Design for networked learning: A case study in health science - Nguyen, Nhung; Terry, Gareth; Kehrwald, Benjamin; Eberhard, Sally; Sim, Kwong Nui; Winters, Annemie; Chanane, Nawal (Proceedings of the International Conference on Networked Learning, 2024)
Higher education (HE) institutions have been transforming dramatically since the pandemic started late 2019 and early 2020. After an initial period of emergency online teaching and learning, HE educators have focused our energy on supporting students’ learning in a complex dynamic learning environment, where digital/online - material/physical - social elements are interwoven and interrelated. Networked learning can be a useful medium for us in this complex context. This paper explores a case study of design for networked learning in a health science postgraduate course. The course was designed in the context of a New Zealand university. The paper will examine how the course design reflects the eight principles of design for networked learning, and proposes some recommendations on design for networked learning at a course level. It links practice and theories, and illustrates how networked learning is unpacked in the context of the course design. While the current paper focuses on the design of the course, it is suggested that future research should conduct an evaluation of the design and develop empirical studies on students’ and teacher’s experience.